Utrophin haploinsufficiency does not worsen the functional performance, resistance to eccentric contractions and force production of dystrophic mice. - Antoine Boulanger Piette; Dounia Hamoudi; Laetitia Marcadet; Frédérique Kyomi Labelle; Rares Ovidiu David; Sabrina Bossé; Anteneh Argaw; Jérôme Frenette (PLoS ONE)
The lack of dystrophin in Duchenne muscular dystrophy (DMD) compromises the integrity and function of muscle fibers. Skeletal muscles, except the diaphragm, do not undergo progressive degeneration in adult mdx mice due to compensatory mechanisms, including structural protein upregulation. New mouse models, including utrophin haploinsufficient mdx (mdx/utrn+/-) mice, may better recapitulate DMD. Our goal was to determine whether mdx/utrn+/- worsens the mdx phenotype and to characterize the course of the disease on muscle function and contractility at 1, 2, and 5 months of age, which encompass all stages of development relevant to DMD therapy. The functional performances of mdx/utrn+/- mice showed that they are not more affected than mdx/utrn+/+ mice based on downhill treadmill running parameters and subsequent recovery measured by open-field voluntary activity. WT mice ran the entire distance (450 m) on the treadmill, with an additional 561 m during the 4 h of open-field while mdx/utrn+/+ and mdx/utrn+/- mice completed, respectively, 236 m and 273 m on the treadmill and 341 m and 287 m during the open-field period. In addition, isolated ex vivo contractile properties and repeated eccentric contractions showed that mdx/utrn+/- does not significantly worsen the function of dystrophic EDL muscles, which are mainly composed of fast-twitch fibers that are preferentially affected in DMD. Twitch, absolute tetanic, and specific tetanic forces were very similar in dystrophic EDL muscles from mdx/utrn+/+ and mdx utrn+/- mice at 1, 2, and 5 months of age. Five-month-old mdx/utrn+/+ and mdx/utrn+/- mice lost roughly 50% of their force due to repeated eccentric contractions. Thus, histological, morphological, biochemical functional and contractile observations showed that utrophin haploinsufficiency has a very limited impact on mdx mice.